A question of balance: a qualitative study of mothers' interpretations of dietary recommendations. - Wood, F; Robling, M; Prout, H; Kinnersley, P; Houston, H; Butler, C (2010)
PURPOSE: Poor nutrition is an increasing problem for economically deprived families, and mothers play a key role in establishing children's diets. We explored mothers' understanding of health-promotion recommendations for healthy eating. METHODS: We conducted qualitative semistructured interviews of 46 mothers within a relatively socioeconomically deprived community. Data were subject to framework analysis. RESULTS: The basic slogans of health promotion were known by mothers and had been adopted into everyday language. Television was the main source of information on dietary advice. Barriers to making changes were due to practical constraints (time, money, family preferences) and a desire to enhance quality of life through enjoyment of food. Although the headline messages of the importance of a healthy diet and what constitutes a healthy diet had reached mothers, misunderstandings were common and led to inappropriate actions. Many descriptions of what mothers reported as a balanced diet would not satisfy official definitions. Some women willfully adapted their understanding of advice to suit their preferences and the reality of their lives and family circumstances. CONCLUSIONS: To provide effective advice and guidance, health professionals need a deeper understanding of how families interpret messages about healthy eating. In addition, they should provide advice based on more individual understandings of diet and take into account patient preferences and life circumstances.